Kund (water tank) adjacent to the Ganesha Temple - Temples of India Project Team (Jio Institute, 2024)
The complex features a kund (water tank) adjacent to the Ganesha Temple. This tank, shaped like a cross, is equipped with steps to reach inside the tank.